Benchmarking specialty hospitals, a scoping review on theory and practice - A. Wind; W. H. van Harten (BMC, 2017)
Abstract Background Although benchmarking may improve hospital processes, research on this subject is limited. The aim of this study was to provide an overview of publications on benchmarking in specialty hospitals and a description of study characteristics. Methods We searched PubMed and EMBASE for articles published in English in the last 10 years. Eligible articles described a project stating benchmarking as its objective and involving a specialty hospital or specific patient category; or those dealing with the methodology or evaluation of benchmarking. Results Of 1,817 articles identified in total, 24 were included in the study. Articles were categorized into: pathway benchmarking, institutional benchmarking, articles on benchmark methodology or -evaluation and benchmarking using a patient registry. There was a large degree of variability:(1) study designs were mostly descriptive and retrospective; (2) not all studies generated and showed data in sufficient detail; and (3) there was variety in whether a benchmarking model was just described or if quality improvement as a consequence of the benchmark was reported upon. Most of the studies that described a benchmark model described the use of benchmarking partners from the same industry category, sometimes from all over the world. Conclusions Benchmarking seems to be more developed in eye hospitals, emergency departments and oncology specialty hospitals. Some studies showed promising improvement effects. However, the majority of the articles lacked a structured design, and did not report on benchmark outcomes. In order to evaluate the effectiveness of benchmarking to improve quality in specialty hospitals, robust and structured designs are needed including a follow up to check whether the benchmark study has led to improvements.